Market orientation and technology orientation: an empirical study on homestay business in West Sumatera - Afifah Afifah; Ranti Komala Dewi (Jurnal Pariwisata Pesona, 2022)
Homestay is one of the supporting elements of the West Sumatra tourism sector. In its development, the homestay business in West Sumatra has not yet achieved the best performance. The orientation of homestay owners to the market (consumers and competitors) and technology are aspects that are not yet clearly implemented, while these two aspects are needed in achieving business performance. This study aims to determine how market orientation and technology are applied by homestay owners. To achieve this goal, the perceptions of 104 homestay owners were collected through questionnaires distributed online and offline. The collected data was then analyzed descriptively. The results show that homestay owners in West Sumatra have implemented market orientation by making customer satisfaction the main goal of running a business and evaluating it regularly. Homestay owners in West Sumatra are also mutually supportive and responsive to competition. The technology orientation aspect has not been implemented thoroughly, where the homestay owner already understands the benefits of technology for his business but has not been able to fully implement it in his business.